Palmprint Recognition Using Gabor Wavelet Transform - Caliskan, Abidin; Ergen, Burhan (Ieee, 2013)
Palmprint recognition system is regarded as the reliable and accurate biometric identification system available. Viewed in the palmprint recognition system of biometric approaches, compared to other models because it is a new handheld biometric feature recognition system has recently attracted the attention of researchers. In this study, palmprint recognition system based on Gabor wavelet transform has been developed. Firstly, image coordinate system is defined to facilitate image alignment for feature extraction. Then, region of interest is cropped from the palmprint images. With developed system feature extracted of region of interest and given of Multi layer perception classifier.
Gabor dalgacik dünüsümü kullanarak avuç içi tanima
21st Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2013 -- CYPRUS
Keywords: Biometric; Palmprint recognition; Gabor wavelet transform; Multi layer perceptron